Development and Characterization of A Plant-Based Jerky from Indonesian Local Crops as A Sustainable Meat Analogue - Anita Carolina Lie Sidarta; Gabriella Charleen; Nicholas Ethan Sunjaya (JFCN: Journal of Food, Culinary, and Nutrition, 2026)
Plant-based meat products have gained increasing attention as sustainable alternatives to animal-based foods. However, achieving a texture comparable to meat remains a major challenge. This study aimed to develop a plant-based jerky using cassava leaves (Manihot esculenta), okra (Abelmoschus esculentus), and sago flour as locally available Indonesian commodities. The product was formulated at a ratio of 2:2:1 (cassava leaves : okra : sago flour) and processed through grinding, steaming, molding, marinating, and cabinet drying. Texture profile analysis showed that the developed plant-based jerky exhibited properties comparable to commercial beef jerky, with hardness values of 2281.3 and 2200.3 gf, respectively. Color analysis revealed L*, a*, and b* values of 23.85, 1.07, and 5.12, respectively. Proximate analysis indicated moisture, carbohydrate, fiber, protein, and fat contents of 17.25%, 59.53%, 13.45%, 5.32%, and 4.45%, respectively. The combination of cassava leaf proteins, okra mucilage, and sago starch successfully produces a compact and chewy structure resembling conventional jerky. These findings demonstrate the potential of local plant-based ingredients to produce an affordable and sustainable jerky alternative, supporting food diversification and the utilization of indigenous agricultural resources